(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | The visual essay is based on research carried out between 2010 and 2015 under the title “Bodies of Crisis—Remembering the German Wende.” The project mainly consisted of oral-history research and a series of performance events presented in the UK and Germany. In 27 interviews, women from East Germany recollected their embodied quotidian experience amidst the political transition from a socialist to a capitalist state in 1989 and thereafter. Live performance opened up access points for a transcultural translation of this experience involving practitioners from diverse cultural and creative backgrounds. The performance work extended the culturally specific experience beyond the East German case by pointing toward global struggles for existence, acceptance, and emancipation. Résumé | Cet essai visuel est le résultat du projet d’études «Bodies of Crisis – Remembering the German Wende» (Corps de la crise – Souvenir de la chute du Mur), réalisé à l’Université de Warwick de 2010 à 2015. Au moyen de 27 interviews, des femmes de l’Allemagne de l’Est se sont remémoré les expériences corporelles de leur vie quotidienne pendant l’époque troublée de 1989 et 1990. Ces interviews ont jeté la base d’un spectacle vivant impliquant des artistes variés, ouvrant un espace d’expression transculturel et artistique de ces expériences de temps de crise. La performance a montré l’universalité des expériences spécifiques de l’Allemagne de l’Est au regard des enjeux mondiaux que sont la survie, la reconnaissance et l’émancipation.